Divergent changes: abstinence and higher-frequency substance use increase among racial/ethnic minority young adults during the COVID-19 global pandemic. (2nd January 2022) - Hicks, Terrell A.; Chartier, Karen G.; Buckley, Tommy D.; Reese, Diamond; Working Group, The Spit for Science; Vassileva, Jasmin; Dick, Danielle M.; Amstadter, Ananda B.; Peterson, Roseann E.; Moreno, Oswaldo
ABSTRACT: Background: Identifying factors influencing substance use among racial/ethnic minorities (REM) is important given the disproportionate impact of the COVID-19 pandemic on this population. Objectives: We examined factors in four domains and hypothesized that poor mental health, negative coping behaviors, negative environmental aspects, and belonging to more vulnerable social groups would be associated with increased substance use during the pandemic. Methods: Multiple regression was applied to longitudinal data from a college sample assessed prior (fall 2017 to spring 2019) and during (spring 2020) the pandemic ( n = 323; 81.5% cisgender women; 34.5% African-American, 36.1% Asian-American, 15.5% Hispanic/Latinx, 11.8% multi-racial) to identify factors predicting current alcohol, cannabis, and nicotine use frequency (spring 2020) and change in frequency of use between springs 2019 and 2020. Results: While infrequent substance use (monthly or less) decreased during the pandemic, abstinence rates increased (alcohol 39%; cannabis 18%; nicotine 18%) and higher-frequency alcohol use increased (207%-1600% 2–3 times+/week) compared to spring 2019. The strongest protective factor was change in living situation during the pandemic, associated with lower current alcohol and cannabis use. Risk factors included a history of trouble with police and impulsivity since the pandemic, both associated with higher current and increased alcohol and cannabis use. REM did not differ on most factors and the outcomes. However, a higher percentage of Asian-Americans than other REM reported living situation changes. Conclusion: Substance use rates diverged during the pandemic, with both increased abstinence and higher-frequency use, attributed mostly to mental health and environmental domain factors with few REM differences.